(untitled) (Applied Biological Research, 2023)
The impact of water pollution on aquatic biota and ecosystem health are determined by the type and degree of water pollution. The present study was aimed to assess the impact of degraded physicochemical regime of river Saraswati in India on the parasitic load of Trichodina sp. obtained from Channa punctatus. The overall water quality status of the polluted river was assessed by using ten physicochemical parameters of water. A total of 404 fish were examined for ciliate ectoparasite Trichodina sp. and prevalence, mean intensity and abundance of parasitic load for each month determined. The parasitic load of Trichodina sp. was significantly (p < 0.001) high in winter and negatively correlated with temperature, free CO2, and biochemical oxygen demand BOD, but positively correlated with electrical conductivity (EC). Fish health was adversely affected by degrading water qualities and parasitic infection. A ‘vicious cycle’ develops because of interplay among deteriorating water quality, withering fish immunological defence, and amplifying parasitic infection.